URBANIZATION AND ITS ENVIRONMENTAL CONSEQUENCES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article studies the environmental impacts of urbanization, focusing on the transformation of natural landscapes into urban areas and the associated consequences for ecosystems, biodiversity, and natural resources. It examines key drivers of urbanization, such as population growth, rural-to-urban migration, and economic development, and their implications for land use, air and water quality, and climate change. Additionally, the article discusses the challenges and opportunities of sustainable urban planning and development, including strategies for mitigating environmental degradation and promoting resilience in urban areas.